MENINGKATKAN KREATIVITAS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK PADA SISWA KELAS IV SDN 318 INPRES PADAKKA - Lolotandung, Reni (Universitas Al-Qolam Malang, 2023)
The purpose of the study was to increase students' creativity with a project-based learning model for class IV at SDN 318 Inpres Padakka. The approach used is an approach with the type of Classroom Action Research (CAR). The research design used is the Kemmis and Mc. Taggart which consists of stages of planning, implementation, observation and reflection. The subjects of this study were fourth grade students of SDN 318 Inpres Padakka consisting of 17 students, eight (8) boys and nine (9) girls. Data collection techniques using observation, documentation, interviews. From the results of the study, it was shown that there was an increase in student creativity with a project-based learning model for fourth grade students at SDN 318 Inpres Padakka with project activities for making planting media from used bottles. This is evident in the first cycle of students who achieved the KKM were ten (10) people or 58.823% and seven (7) students or 41.176% who had not reached the KKM. Meanwhile, in the second cycle, the students' creativity results in achieving the KKM 70 were fifteen (15) people or 88.235% and those who did not reach the KKM were two (2) people or 11.764%. Thus, in the second cycle, students' creativity increased with the Project-Based Learning Model.